Pengaruh Kualitas Pelayanan, Athmosphere Store, Bundling Product dan Point Of Purchase terhadap Impulsive Buying Melalui Corporate Image Sebagai Variabel Intervening - Muhamad Yusup Ginanjar Trisnadi; Ade Komaludin; Edy Suroso (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This research aims to examine the influence of service quality, Atmosphere Store, bundling product and point of purchase to Impulsive buying through Corporate image as an intervening variable. The study was conducted on Alfamart Members in the North Ciamis Region. Sampling is carried out using techniques propotioned stratified random sampling, with a total sample size of 210 samples, spread across 16 Alfamart stores in the North Ciamis Region. The research instrument used was a questionnaire with a Likert scale. The analysis technique used is structural equation modeling with the smartPLS application. The results of this research show that, 1) Service quality is in good condition, whereas Atmosphere Store, Bundling product, Point of purchase, Corporate image and Impulsive buying in very good condition; 2) Quality of service, Atmosphere Store, Bundling product and Point of purchase positive and significant effect on Corporate image; 3) Quality of service, Atmosphere Store, Bundling product and Point of purchase positive and significant effect on Impulsive buying; 4) Corporate image positive and significant effect on Impulsive buying; 5) Quality of service, Atmosphere Store, Bundling product and Point of purchase influence on Impulsive buying through Corporate image as an intervening variable.